Bank lending channel and household consumption expenditure in Nigeria - Onanuga, Abayomi Toyin; Arikewuyo, Kareem Abidemi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2024)
The main objective of this paper is to determine the effect of bank lending channel on household consumption expenditure in Nigeria. The influence of the channel as a transmission route to household consumption has not been relatively investigated in many developing nations like Nigeria. In view of this, the aim of the study is achieved using the non-linear econometric approach such as the Generalized Method of Moments (GMM) on annual secondary data obtained from the United Nations Statistical Division Database and Central Bank of Nigeria Database. The study found that lending rates in maximum and prime are significantly affect real household consumption expenditure in Nigeria. In addition, evidence from the study suggest that growth rate of the per capita income and changes in the domestic prices of nominal output significantly affect the response variable The study discussed the implications of the study for the bank lending channel with policy recommendations.